2021
DOI: 10.3390/life11121326
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Cold Environment on the Performance of Professional Cyclists: A Pilot Study

Abstract: The practice of physical activity in a variable climate during the same competition is becoming more and more common due to climate change and increasingly frequent climate disturbances. The main aim of this pilot study was to understand the impact of cold ambient temperature on performance factors during a professional cycling race. Six professional athletes (age = 27 ± 2.7 years; height = 180.86 ± 5.81 cm; weight = 74.09 ± 9.11 kg; % fat mass = 8.01 ± 2.47%; maximum aerobic power (MAP) = 473 ± 26.28 W, under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…In studies of human muscle activity, information such as temperatures of skin and muscle have an apparent effect on the sEMG signals [9][10][11][12][13][14]. Figuring out this effect is crucial and may provide additional guidance for the muscle thermotherapy [15][16][17] and cryostimulation therapy [18][19][20][21][22][23][24]. To fulfill the need of temperature measurement, incorporating resistance temperature sensors into the electronic skin patch with electrodes is a simple yet efficient solution.…”
Section: Introductionmentioning
confidence: 99%
“…In studies of human muscle activity, information such as temperatures of skin and muscle have an apparent effect on the sEMG signals [9][10][11][12][13][14]. Figuring out this effect is crucial and may provide additional guidance for the muscle thermotherapy [15][16][17] and cryostimulation therapy [18][19][20][21][22][23][24]. To fulfill the need of temperature measurement, incorporating resistance temperature sensors into the electronic skin patch with electrodes is a simple yet efficient solution.…”
Section: Introductionmentioning
confidence: 99%
“…On day 7, participants reported to the lab in the evening (≥ 16:00), had a venous blood and urine sample collected, consumed a telemetric temperature pill (E-celsius Performance Pill, Body Cap, France) and performed a battery of cognitive function tests. Although the timing of pill ingestion (1 – 12 h before) does not appear to interfere with the validity of the sensor [ 47 ], consistent with previous studies, we provided the pill 5–8 h before our first recording [ 46 , 48 ], to ensure passage from the stomach. These telemetric pills have been shown to have excellent reliability and validity [ 49 ] and are considered the industry standard for temperature monitoring [ 50 ].…”
Section: Methodsmentioning
confidence: 85%
“…In this sense, breathing air at 23 °C compared to 33 °C improves performance capacity and reduces discomfort [ 9 ]. Last but not least, a pilot study suggested that in cold environmental conditions, the running performance was reduced [ 11 ].…”
mentioning
confidence: 99%
“…The papers published in this Special Issue discuss the topics of greatest concern to the population and the scientific community from the perspective of human thermophysiology. Most of the articles evaluate how the physiological response during or after exercise is affected by extreme environmental conditions, such as high temperatures [ 7 ], hot and humid environments [ 8 , 9 ], dehydration status [ 10 ] or even cold environments [ 11 ]. This issue is of concern to society as a whole, since global warming is an established threat, greatly impacting our environment [ 12 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation